THE RETRIEVAL METHOD OF EFFECTIVE PARAMETERS FOR ACOUSTIC METAMATERIALS - Ismagulov, Temirlan (Nazarbayev University School of Sciences and Humanities, 2025)
Efficient, broadband characterization of acoustic metamaterials is essential for trans- lating their extraordinary wave-manipulation capabilities into practical devices. Here we present a robust retrieval framework that extracts key effective parameters directly from two-port scattering measurements acquired in a 1D circular waveguide: acoustic impedance Zeff, refractive index neff, dynamic mass density ρeff, and dynamic Young’s modulus Eeff. The expressions for effective parameters are obtained using reflection and transmission through a homogeneous slab by summing the infinite series of internal multiple reflections. A Kramers-Kronig branch selection rule is then implemented to enforce passivity and continuity of neff across frequency, eliminating ambiguity in the complex-logarithm inversion. The proposed method provides a fast route to quantify dispersive parameters in acoustic metamaterials, offering a valuable tool for the design of cloaks, lenses, and noise-control elements.
Keywords: NATURAL SCIENCES::Physics; TECHNOLOGY::Engineering physics::Acoustics; Metamaterials; type of access: open access